Spatial and temporal analysis of notified cases of congenital syphilis in the state of Ceará in the period from 2008 to 2018 (Research, Society and Development, 2022)
Objective: To analyze the spatial and temporal distribution of notified cases of congenital syphilis in the state of Ceará from 2008 to 2018. Method: Ecological study, with temporal and spatial analysis performed from data on congenital syphilis in the state of Ceará in the period of 2008 to 2018. Results: The number of cases showed an increasing trend, with an inflection point in the year 2012 (AAPC= +12.3; p